Precise determination of gravity in geodetic networks in Slovakia – CBA2G approach - ZAHOREC, Pavol; PAPČO, Juraj; JANČOVIČOVÁ, Miroslava; MARUŠIAK, Ivan; PAŠTEKA, Roman (Contributions to Geophysics and Geodesy, 2025)
We present software for calculating gravity acceleration at points of levelling networks in Slovakia. The chosen approach uses an existing detailed gravimetric database and a back-calculation (reconstruction) of the gravity acceleration from the Bouguer anomaly map. We analyse the accuracy of this approach on a sample of independent geodetic points as well as in-situ control measurements.